Identification Of Spot Diving As A Recreational Sport In Mandeh Area - Ricky Nanda Pratama (International Journal of Tourism, Heritage and Recreation Sport, 2020)
The problem in this research is that there is no related information regarding the identification and mapping of diving spots in the Mandeh area. This study aims to identify and map diving spots as a recreational sport in the Mandeh area. This type of research is descriptive, which aims to describe and map the Diving Spot as a recreational sport in the Mandeh area. Data analysis techniques in this study are data collection, data reduction, data display / data presentation, and drawing conclusions and then verification. Data collection techniques in this study were observation, interview, and documentation. The results revealed that based on the results obtained, it can be concluded that the Mandeh area has several beautiful diving spots and has historical value. This is evidenced by the results of research where researchers found five diving spots in the Mandeh area, namely Boelongan which is famous for its history, namely MV Boelongan Nederlan which sank in 1942, then Batu Buayo which is identified with its beautiful and unique coral reefs, the Montipora Aquituberculata type, namely coral which is thin and resembles a barrel or funnel, next is Marak Agate where there are turtles and sea anemones, then Marak Labuan which has coral type Coral Foliose, which is the type of growth such as leaves and fungi, then Pagang Dermaga there is planting coral species Acropora Digitata with speda media and accompanied by a school of Scooling Fish, all of which are for recreational sports.